TIDES AND TIDAL CURRENTS IN THE ANTARCTIC SEA OBSERVED AT SYOWA STATION, EAST ANTARCTICA - オダマキ, ミノル; オオカ, カツジロウ; ODAMAKI, Minoru; OKA, Katsujiro (National Institute of Polar Research, 1990)
P(論文) Tidal currents were observed at the Kita-no-seto Strait near Syowa Station for 15 days from January to February, 1982 by the 23rd Japanese Antarctic Research Expedition. The observed currents show a semidiurnal type in contrast with the tides at Syowa Station showing a mixed type. Judging from the amplitude and phase lag distributions around Antarctica, M2 tidal wave is understood as a standing wave which has a node near the Station. Therefore, the disagreement of the characteristics is interpreted as that the vertical oscillation (tide) is reduced and the horizontal movement (tidal current) becomes significant around the node. K1 tidal wave is understood as a progressive wave which is trapped to the Antarctic coast and traveling from east to west once a day around Antarctica. This understanding agrees with the fact that the phase lag of K1 tidal current at the Strait is close to that of K1 tide at Syowa Station. departmental bulletin paper